How does the Philippine peso exchange rate respond to inflation, industrial production and trade balance? A Granger causality analysis - Romero, Frederick P. (Animo Repository, 2017)
© 2017 American Scientific Publishers All rights reserved. In a country’s overall growth and economic activity, the foreign exchange rate plays an important role in affecting both variables. This paper investigated how the exchange rate movement can be influenced by macroeconomic variables namely: inflation, industrial production and trade balance. Times series monthly data is collected from January 1998 to December 2014. To test the stationarity of the data, the paper utilized the Augmented Dickey Fuller (ADF) test. In addition, the study used LaGrange-Multiplier Test of ARCH Test and Exponential Generalized Autoregressive Conditional Heteroskedasticity (EGARCH) in examining heteroscedasticity in the data used. Finally, the study used the Granger Test for Causality in calculating the long-run dynamic relationship between the macroeconomic variables and the exchange rate. The study concludes that the Philippine peso exchange rate is not influenced by the terms of inflation, trade balance and industrial production level. The research showed that there is no significant relationship between exchange rate and the macroeconomic variables for the period covered. The implication of this study suggests that policy makers on monetary policies should look at other factors aside from the macroeconomic variables used in this paper that may provide significant effect on the movement of the exchange rate in the Philippines.